2020
DOI: 10.5334/aogh.3005
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Healthcare Workers in China for COVID-19 Epidemic

Abstract: Background Coronavirus disease 2019 (COVID-19) is a new infectious disease caused by SARS-CoV-2, with epidemiological characteristics such as strong infectivity, high morbidity, multiple infection routes, and widespread infection [1, 2]. Since the epidemic began in Wuhan, China, in December 2019, from January 2020 to April 2020, COVID-19 has spread explosively in China. As of May 24, a total of 5,290,506 cases had been diagnosed worldwide, with a total of 342,448 deaths. A total of 84,525 cases had been diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 16 publications
3
57
1
2
Order By: Relevance
“…One hundred studies reported on factors associated with psychological symptoms during infectious disease outbreaks. Female sex (compared to male) was the factor most commonly associated with worse psychological symptoms in physicians [ 30 , 41 , 44 , 48 , 63 , 66 , 71 , 77 , 89 , 98 , 112 , 122 , 127 , 128 , 138 , 142 , 144 , 148 , 163 , 165 , 170 , 174 – 189 ]. Other factors associated with poorer psychological outcomes included direct patient contact [ 28 , 32 , 34 , 44 , 46 , 53 , 59 , 64 , 71 , 81 , 95 , 98 , 112 , 122 , 130 , 163 , 169 , 175 , 182 , 183 , 186 , 190 – 192 ] [ 30 , 34 , 41 , 44 , 48 , 59 , 63 , 66 , 71 , 77 , 89 ], single marital status (compared to married) [ 39 , 44 , 59 , 63 , 98 , 122 ], younger age [ 33 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred studies reported on factors associated with psychological symptoms during infectious disease outbreaks. Female sex (compared to male) was the factor most commonly associated with worse psychological symptoms in physicians [ 30 , 41 , 44 , 48 , 63 , 66 , 71 , 77 , 89 , 98 , 112 , 122 , 127 , 128 , 138 , 142 , 144 , 148 , 163 , 165 , 170 , 174 – 189 ]. Other factors associated with poorer psychological outcomes included direct patient contact [ 28 , 32 , 34 , 44 , 46 , 53 , 59 , 64 , 71 , 81 , 95 , 98 , 112 , 122 , 130 , 163 , 169 , 175 , 182 , 183 , 186 , 190 – 192 ] [ 30 , 34 , 41 , 44 , 48 , 59 , 63 , 66 , 71 , 77 , 89 ], single marital status (compared to married) [ 39 , 44 , 59 , 63 , 98 , 122 ], younger age [ 33 ...…”
Section: Resultsmentioning
confidence: 99%
“…The six included qualitative studies [56,72,74,115,204,209] were considered to be of sufficient methodological quality. One study had a pre-test, post-test study design and was considered to be of sufficient methodological quality [112].…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…In the context of the COVID-19 pandemic, health professionals showed higher levels of anxiety, stress and depression [ 6 , 7 ] than those of the general population [ 3 , 8 , 9 , 10 ]. However, other studies have shown that the prevalence of anxiety and depression among health professionals and the general population in COVID-19 context was similar [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large number of patients with COVID-19 around the world, many countries have asked interns, and even professors and residents, to join the workforce and treat the patients. However, the lack of sufficient experience and knowledge in medical students in such critical situations can be very stressful (12,13). A study in China found that 27% of medical students who lacked sufficient experience in dealing with such crises and entered the medical environment as workforce experienced psychological distress, and 11% suffered from mental disorders such as post-traumatic stress disorder (PTSD) (14).…”
Section: Introductionmentioning
confidence: 99%